TINGKAT PENERAPAN PERTANIAN ORGANIK DAN POLA PERILAKU KOMUNITAS PETANI SAYUR ORGANIK DI KECAMATAN TRAWAS KABUPATEN MOJOKERTO - Kholifatus Saadah; Sudarko Sudarko; Lenny Widjayanthi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
Vegetables provide nutrients for health and maintenance of human body. Apart from this fact about its nutrient-content, human also need to make sure the vegetables they consume are chemical free. The most important factor in running this organic farming system is farmers’ behavior over the system itself. This behavior, supported by the farmers’ knowledge about the farming system, will lead to their demeanor in applying the farming system in Trawas. This research uses three methods; descriptive method, correlation method and analytic method. To collect the sample, Simple Random Sampling is used. From 104 members of the community, by using Slovin’s formula, the researcher gets 31 respondents as the samples. Furthermore, the researcher uses scoring and Rank Spearman method in the analysis. The result of this research shows that; 1) the rank of the farmers’ behavior are average, and the rank of the knowledge are also average (54,84%), while the rank of the demeanor are high (64,52%), and the rank of the skills are high (64,52%); 2) the rank of the application of the organic farming system in Trawas is high (54,84%); 3) there is corelation between knowledge, demeanor and skill with the application of organic system in District of Trawas at the 99% rate of signification. Keywords : Organic Farming, Farmer Behavior, Vegetables Farming